consolidation of territorial and maritime rights in the arctic: Analysis of a historic and uninterrupted practice of pacific resolution for the effective enjoyment of rights (2017)
This article addresses the historic process leading to the construction of a legal regime governing the exercise of sovereignty over the arctic lands and islands as well as the current and pending process for the consolidation of sovereign rights over the continental shelf beyond 200 nautical miles. As his main working hypothesis, the author submits that the current claims to an extended continental shelf can be framed and are substantiated coherently with the approach adopted for the definition of territorial titles of the lands and islands in the Arctic. This articles seeks to complement the current literature by visualizing the existence of a real historic artic practice of peaceful settlement of the most important disputes. © 2017 Universidad de Talca.